Psychosocial predictors of academic achievement of adolescents: practical reference on employment of SEM: examining variables that were predictive of adolescents’ academic achievement - Ismail, Khamsiah; Abdul Rahman, Shukran; Abdul Majid, Hariyati Shahrima (Lambert Academic Publishing, 2012)
Social and educational psychology have been concerned with analysing the variables that are both associative and predictive of adolescents’ academic achievement as high achievement is believed to indicate excellent performance in school and promote better opportunities for selection of preferred academic specializations and subsequent career selection. This longitudinal study was designed to determine the magnitude of the variables in predicting their achievements. Proposed model and competing model in this longitudinal study had consistently illuminated career aspiration as a more dynamic variable, both as a predictor and as a mediator between career-related construct and academic achievement. This study provides implications that schools, counsellors, teachers and parents can exert a powerful influence on the career development of adolescents as the school is believed to be the most important venue where students learn to bridge education and the world of work. Parents can also encourage and support their adolescents’ efforts to obtain good academic achievement by helping and supporting their career plan.